Heterotopic Pancreas in the Stomach: A Case Report and a Brief Review of the Literature - Gokhale, Uday A; Nanda, Annu; Pillai, Rajasekharan; Al-Layla, Dhia (JOP. Journal of the Pancreas, 2010)
Context Heterotopic pancreas is the presence of pancreatic tissue found outside the usual anatomical location of the pancreas. It is a rare condition and can occur anywhere in the gastrointestinal tract with the stomach and the small bowel being the most common sites. It is usually asymptomatic and often discovered incidentally. Case report We report the case of a 48-year-old Omani female who presented with recurrent epigastric pain. Endoscopy revealed a sessile mass in the antrum which was snared and showed heterotopic pancreatic tissue in the submucosa on histopathology. Conclusion Heterotopic pancreas should be considered in the differential diagnosis of gastric mass lesions. Image: Solid, sessile polypoid mass under the intact overlying mucosa in the gastric antrum.